Apalutamide and its use in the treatment of prostate cancer. (14th November 2018) - Borno, Hala T; Small, Eric J
High-risk nonmetastatic castration-resistant prostate cancer is a lethal disease that previously lacked clear treatment options. Progression to bone metastases is associated with significant morbidity and high cost. Apalutamide, an androgen receptor inhibitor, has substantial clinical response in nonmetastatic castration-resistant prostate cancer. Apalutamide + androgen deprivation therapy is well tolerated and improves metastasis-free survival, progression-free survival and time to symptomatic progression, and is associated with a favorable trend of improved overall survival. Future research is needed to elucidate mechanisms of resistance to treatment with androgen signaling inhibitors.